Evaluation, Awareness, Practice and Management of Cold Chain at the Primary Health Care Centers in Coastal South India - Rao, S; Naftar, S; Baliga, s; Unnikrishnana, B (Journal of Nepal Paediatric Society, 2012)
Introduction: Vaccination is one of the most effective disease prevention strategies and potency of vaccines is dependent on effective management of cold chain at all levels of vaccine handling. The objective was to assess the status of cold chain at the primary health centers and to assess the knowledge and practices of medical officers at these centers regarding cold chain management. Materials and Methods: This cross sectional study was conducted at 70 primary health centers of Dakshina Kannada District of Coastal South India. Cold chain equipment and maintenance process was noted following direct observation on uninformed visits. Data regarding the knowledge and practices of cold chain management was obtained by interviewing the medical officers using structured pretested questionnaire. Results: Ice lined refrigerators and deep freezers were available in 69 (98.6%) and 67(95.8%) of centers. Dial thermometer was present in all the centers. Cold boxes, frozen packs and automated voltage stabilizers were available in 68(97.2%) centers. Improper vaccine storage was observed in 7 (10%) centers. Majority of medical officers had knowledge and correct practices in fields like ideal equipment, OPV administration, vaccine requiring diluents but only 47 (61.8%) medical officers had correct practice of defrosting the deep freezers. Conclusions: The availability of equipment is near universal. Improper vaccine storage practices and poor knowledge in some fields of cold chain management may adversely affect the quality of administered vaccine. Relevant training for those handling the cold chain is recommended. Key words: Cold Chain; India; Primary health center; Temperature monitoring DOI: http://dx.doi.org/10.3126/jnps.v32i1.5946 J. Nepal Paediatr. Soc. Vol.32(1) 2012 19-22